Management of conduction disorders after transcatheter aortic valve implantation: results of an EHRA survey. (19th May 2022) - Badertscher, P; Knecht, S; Zeljkovic, I; Sticherling, C; De Asmundis, C; Conte, G; Kuehne, M; Boveda, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Left bundle branch block (LBBB) is common after transcatheter aortic valve implantation (TAVI) and is an indicator of subsequent high-grade atrioventricular block. Consensus regarding a reasonable strategy to manage cardiac conduction disturbances after TAVI has been elusive Methods: The European Heart Rhythm Association (EHRA) conducted a survey to capture contemporary clinical practice for conduction disorders after TAVI. A 25-item online questionnaire was developed and distributed among the EHRA electrophysiology research network centres. Results: Of 117 respondents, 44% were affiliated with university hospitals. This survey has revealed that a standardized management protocol for advanced conduction disorders such as LBBB or AVB after TAVR is available in 63% of participating centres. Telemetry was chosen by most participants as the most frequent management strategy for patients with new or preexisting LBBB after TAVI (79%, 70%, respectively, Figure 1). Duration of telemetry in patients with new LBBB varied: 18% chose 24 hours, 35% 48 hours, 27% 72 hours and 20% ≥ 72 hours. Similarly, in patients with new LBBB after TAVI undergoing EP study, the cut-off for a prolonged HV interval for PM implantation was heterogenous among European centers (7.4% ≥ 55ms and 44% ≥ 75ms). Conduction system pacing was chosen as preferred device therapy in patients with LBBB and normal LVEF in 3.7% and in patients with LBBB and reduced LVEF in 5.6%. Conclusions: The management of conduction disorders after TAVI is very heterogeneous across European centres. Risk stratification strategies vary substantially. The role of conduction system pacing in patients with LBBB after TAVI needs to be defined. There is a considerable room for better uniformity in clinical practice.